Strategi Penetapan Harga Komoditas Dalam Perspektif Ekonomi Syariah - Sholikul Hadi (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2019)
Price has a very important role for the survival of the company. The strategy of fixing commodity prices is widely discussed in conventional economics, as well as its application has been done both to maintain its business and to compete to win the market. However, whether the pricing strategy is in accordance with the rules of Islamic law. The research objectives that compilers want to achieve are to determine the strategy for fixing commodity prices in the perspective of Islamic economics, as well as the role of the government in dealing with price problems in the market. This research is a library research design using a secondary analysis approach. This approach is divided into two stages, namely the descriptive stage and the evaluative stage. Instrument and data collection techniques used are documentation methods. The data analysis technique used is qualitative analysis techniques with a literature approach which is carried out using three product components, namely data reduction and data collection, display data, and conclusion drawing, namely reducing and collecting various data and theories related to the central theme with various sources. as well as classifying them to be described systematically, then a study and discussion is carried out to then draw conclusions on the problem under study. The results showed that the strategy of fixing commodity prices in the perspective of Islamic economics can be applied by looking at market conditions, both supply and demand. Unlike the principles of commodity pricing strategies in conventional economics which have the ultimate goal of maximizing profit and seeking profit for the purpose of accumulating wealth. Islamic economic principles in prices, namely to improve the welfare of society in terms of income distribution. The market mechanism does not always work according to the existing concept, thus the role of the government as a supervisory body is needed in dealing with price problems in the market in order to avoid market distortion problems. However, the government is prohibited from intervening when the market is running normally.